2014
DOI: 10.1016/j.nano.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Culture-free diagnostics of Pseudomonas aeruginosa infection by silver nanorod array based SERS from clinical sputum samples

Abstract: Pseudomonas aeruginosa can cause major infection in immunocompromised patients, and successful antibiotic treatment of the infection relies on accurate and rapid identification of the infectious agents. Here, we reported a culture-free diagnostic method based on the surface-enhanced Raman spectroscopy (SERS) of pyocyanin (PCN), a major biomarker of P. aeruginosa. This platform can detect PCN as low as 5 ppb or 2.38 × 10−8 mol L−1 in both aqueous solutions and spiked clinical sputum samples. It has also been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 36 publications
3
71
1
Order By: Relevance
“…PC1 loading plot (Figure 6A) generated from the analysis of the SERS image from a 2-day FRD1 pellicle biofilm (Figure 6B) reveals features at ~1352, 1511, 1572 and 1600 cm −1 . 22 These high z-score features resemble SERS bands representing a combined C-C/C-N stretch and C-H bend at 1352 cm −1 , C-C stretch, CH 3 wag and C-H in-plane bend at 1511 cm −1 present in the SERS spectrum of pyocyanin standard 33 (Figure 6A inset).…”
Section: Resultsmentioning
confidence: 85%
“…PC1 loading plot (Figure 6A) generated from the analysis of the SERS image from a 2-day FRD1 pellicle biofilm (Figure 6B) reveals features at ~1352, 1511, 1572 and 1600 cm −1 . 22 These high z-score features resemble SERS bands representing a combined C-C/C-N stretch and C-H bend at 1352 cm −1 , C-C stretch, CH 3 wag and C-H in-plane bend at 1511 cm −1 present in the SERS spectrum of pyocyanin standard 33 (Figure 6A inset).…”
Section: Resultsmentioning
confidence: 85%
“…It is a member of the quorum sensing system of Pseudomonas aeruginosa and is used as a biomarker for this bacteria species. The first study about the detection of pyocyanin in biofluid samples with SERS was performed by Wu et al [64] in 2014. Pyocyanin was detected in clinical sputum samples with 95.6% sensitivity and 93.3% specificity using a silver nanorod array as the SERS substrate.…”
Section: Detection Of Quorum Sensing Moleculesmentioning
confidence: 99%
“…Algae biofilms contain a polysaccharide-rich matrix Bacteria biofilms contain a protein-rich matrix [60] Escherichia coli Staphylococcus aureus DNA/RNA components (678, 802, and 1570 cm −1 ) [22] Escherichia coli Distinctive spectral features for monitoring bacterial death (DNA/RNA components, 678 cm −1 ) [61] Pseudomonas aeruginosa Detection of pyocyanin (1088, 1125, 1352 and 1613 cm −1 ) [64] Pseudomonas aeruginosa Plasmonic substrates were fabricated and used in label-free detection of pyocyanin [65] Pseudomonas aeruginosa C-C stretch, C-N stretch, and C-H in-plane bend modes were assigned as a marker peak of pyocyanin [66] Brevundimonas diminuta Staphylococcus aureus …”
Section: Type Of Microorganism Outputmentioning
confidence: 99%
“…In one of the pioneering works in this area, Costas and coworkers used a film of gold nanoparticles bound to protein receptors to detect quorum sensing activity in situ [53]. Previously, the majority of SERS studies of quorum sensing have been restricted to the measurement of liquid samples, rather than observation of quorum-sensing processes in situ [52,53,56]. Recent work in the area of micro-and nanostructured plasmonically-active substrates has shown that measurement of quorum sensing signals can also be achieved on patterned surfaces [54].…”
Section: Concept: Sers Detection Of Quorum Sensing For Early Stage Momentioning
confidence: 99%